2021
DOI: 10.1016/j.clinimag.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of severity in coronavirus disease (COVID-19) using quantitative CT imaging

Abstract: Purpose To evaluate whether the extent of COVID-19 pneumonia on CT scans using quantitative CT imaging obtained early in the illness can predict its future severity. Methods We conducted a retrospective single-center study on confirmed COVID-19 patients between January 18, 2020 and March 5, 2020. A quantitative AI algorithm was used to evaluate each patient's CT scan to determine the proportion of the lungs with pneumonia (VR) and the rate of change (RAR) in VR from sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Using a cut-off value of 22.6%, the percentage of pneumonia volume showed good performance (AUC of 0.868) for predicting critical illness with a sensitivity and specificity of 81.3% and 80.6%, respectively. Li et al also found that the proportion of lungs with pneumonia measured by a deep learning-based algorithm predicted COVID-19 patients who later developed severe disease ( 24 ). They suggested that a CT scan performed as early as five days after the initial onset of symptoms can be used to identify patients who may progress to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using a cut-off value of 22.6%, the percentage of pneumonia volume showed good performance (AUC of 0.868) for predicting critical illness with a sensitivity and specificity of 81.3% and 80.6%, respectively. Li et al also found that the proportion of lungs with pneumonia measured by a deep learning-based algorithm predicted COVID-19 patients who later developed severe disease ( 24 ). They suggested that a CT scan performed as early as five days after the initial onset of symptoms can be used to identify patients who may progress to severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of quantitative techniques have been used to quantify COVID-19 infection in the early phase, ranging from simple densitometry to deep learning methods (95,96). Quantitative CT (QCT) assessment of severity of COVID-19 infection in the early phase of infection is an independent predictor of ICU admission and of mortality (97)(98)(99). QCT may also be used to assess sequential change in lung volumes and pulmonary opacity (99).…”
Section: Potential Role For Quantitative Imaging In Post-covid Lung Diseasementioning
confidence: 99%
“…To appraise COVID-19 infection in the initial phase, different techniques are used, including densitometry and deep learning methods [ 30 , 31 ]. Early phase quantitative CT assessment of severity is an autonomous forecaster of ICU hospitalization and mortality [ [32] , [33] , [34] ]. It could as well be used to appraise serial variations in lung volumes and pulmonary opacity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%